2014
DOI: 10.1111/cup.12379
|View full text |Cite|
|
Sign up to set email alerts
|

Primary cutaneous follicle center lymphoma with Hodgkin and Reed‐Sternberg‐like cells: a new histopathologic variant

Abstract: Primary cutaneous follicle center lymphoma (PCFCL) is the most frequent cutaneous B-cell lymphoma. A 62-year-old man presented with a solitary indolent subcutaneous nodule for 3 years duration, without other abnormalities. Histological examination showed lymphoproliferation with a nodular growth pattern characterized by fibrous collagen bands surrounding nodules. The nodules were composed of medium-sized centrocytes admixed with many large multilobulated and lacunar cells without eosinophils or granulomatous a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 19 publications
0
11
0
1
Order By: Relevance
“…Among malignancies, CD30-positive T-cells typically characterize lymphomatoid papulosis (LyP) and primary cutaneous anaplastic large cell lymphoma (cALCL) [ 1 , 36 ], whereas in B-cell neoplasms CD30-positive cells are less common, occurring in the setting of iatrogenic immunosuppression (i.e., mucocutaneous ulcers) [ 1 , 37 ], and in primary cutaneous diffuse large B-cell lymphomas (DLBCL) [ 38 ]. CD30 expression has also been reported in a variable number of neoplastic cells of primary cutaneous follicle center lymphoma (PCFCL) and of primary cutaneous marginal zone lymphoma (PCMZL) [ 14 , 15 , 39 , 40 , 41 , 42 ], with rare cases describing a Hodgkin and Reed–Sternberg (H/RS)-like morphology [ 26 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among malignancies, CD30-positive T-cells typically characterize lymphomatoid papulosis (LyP) and primary cutaneous anaplastic large cell lymphoma (cALCL) [ 1 , 36 ], whereas in B-cell neoplasms CD30-positive cells are less common, occurring in the setting of iatrogenic immunosuppression (i.e., mucocutaneous ulcers) [ 1 , 37 ], and in primary cutaneous diffuse large B-cell lymphomas (DLBCL) [ 38 ]. CD30 expression has also been reported in a variable number of neoplastic cells of primary cutaneous follicle center lymphoma (PCFCL) and of primary cutaneous marginal zone lymphoma (PCMZL) [ 14 , 15 , 39 , 40 , 41 , 42 ], with rare cases describing a Hodgkin and Reed–Sternberg (H/RS)-like morphology [ 26 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][16][17][18][19] The most recent studies showed an incidence of <0.5% of skin infiltration. 15 The marked decrease in the (eg, primary cutaneous follicle center and cutaneous marginal zone lymphoma) [25][26][27] (summarized in Table 3). LyP is characterized by the presence of small papules or nodules, with or without ulceration, that spontaneously heal with scarring, over the course of weeks.…”
Section: Discussionmentioning
confidence: 99%
“…The proliferative index Ki67 in the PCFCL was estimated at 20%. PCR and FISH studies did not detect the presence of the t (14; 18) translocation [ 30 ]. The comparison between these two isolated cases may suggest that the PCFCLs associated with H/RS cells have low-proliferation rates and appear clinically indolent.…”
Section: Discussionmentioning
confidence: 99%